2001
DOI: 10.1021/bi0106989
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Antagonist Binding Site of the Serotonin Type 3 Receptor by Fluorescence Resonance Energy Transfer

Abstract: We have measured fluorescence resonance energy transfer (FRET) between a fluorescent antagonist, bound to the purified detergent-solubilized serotonin type 3 receptor, and a lipophilic acceptor probe partitioned into the micelle surrounding the detergent-solubilized receptor. The experimentally observed FRET efficiency was evaluated on the basis of the characteristic dimensions of the receptor-micelle complex and the average number of acceptor molecules in such micelles. The binding site was determined to be 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In earlier work from our group, the binding of a fluoresceinlabeled, high affinity competitive antagonist 1,2,3,9-tetrahydro-3-[(5-methyl-1H-imidazol-4-yl)methyl]-9-(3-amino-(N-fluorescein-thiocarbamoyl)-propyl)-4H-carbazol-4-one (GR-flu) to the 5-HT 3 receptor has been characterized by steady state (9,10) and time-resolved (11) fluorescence spectroscopy. These studies indicated that receptor-bound GR-flu senses a local environment, which is ϳ0.8 pH units more acidic than the bulk, suggesting that acidic residues, glutamate or aspartate, are located close to the binding site of GR-flu.…”
mentioning
confidence: 99%
“…In earlier work from our group, the binding of a fluoresceinlabeled, high affinity competitive antagonist 1,2,3,9-tetrahydro-3-[(5-methyl-1H-imidazol-4-yl)methyl]-9-(3-amino-(N-fluorescein-thiocarbamoyl)-propyl)-4H-carbazol-4-one (GR-flu) to the 5-HT 3 receptor has been characterized by steady state (9,10) and time-resolved (11) fluorescence spectroscopy. These studies indicated that receptor-bound GR-flu senses a local environment, which is ϳ0.8 pH units more acidic than the bulk, suggesting that acidic residues, glutamate or aspartate, are located close to the binding site of GR-flu.…”
mentioning
confidence: 99%
“…It has been used previously to analyze such distances between interacting soluble proteins (Garzon-Rodriguez et al, 1997;Rye, 2001) and between a soluble molecule and a purified, reconstituted membrane protein (Li et al, 1999;Vallotton et al, 2001). Site-directed spin-labeling has been used in a similar manner (Hubbell et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] FRET measurements have become widespread owing to the recent implementations for microscopic and flow cytometric setups. [12][13][14][15][16] Measurements usually involve detecting the quenching of donor fluorescence in the presence of acceptors [17,18] or scaling of sensitized emission of the acceptor to total unquenched donor intensity. [12,19] There are also several methods that measure the fluorescence lifetime of the donor [20,21] or changes in the bleaching kinetics of the donor fluorescent signal caused by FRET.…”
Section: Introductionmentioning
confidence: 99%